2012
DOI: 10.1212/cpj.0b013e31824c6cbd
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric epilepsy

Abstract: Epilepsy in children can be very different from epilepsy in adults, both in seizure type and epilepsy syndrome. The goal in treating children is seizure freedom, no treatment side effects, and function that is no different from the general population. In a significant percentage of patients, this goal remains unachievable, but many aspects of epilepsy are becoming clearer. This review will highlight 5 areas where progress is being made to achieve these goals in pediatric epilepsy. Specific research animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…These differences may be related to types of seizure and epilepsy syndrome. 11 Clinicians should take a comprehensive and neurologically focused history and conduct thorough clinical examination. This is important for both diagnosis and management of epilepsy in children.…”
Section: Epilepsy In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may be related to types of seizure and epilepsy syndrome. 11 Clinicians should take a comprehensive and neurologically focused history and conduct thorough clinical examination. This is important for both diagnosis and management of epilepsy in children.…”
Section: Epilepsy In Childrenmentioning
confidence: 99%
“…8 The objectives of treatment of epilepsy in children include providing freedom from seizures without adverse events and helping patients achieve overall function similar to their age-specific population. 11 Three important types of seizures in children, namely, febrile seizures, juvenile myoclonic epilepsy, and absence epilepsy are discussed below.…”
Section: Epilepsy In Childrenmentioning
confidence: 99%
“…Sekitar 50 juta orang di dunia menderita epilepsi, menjadikan epilepsi sebagai beban bagi pelayanan kesehatan (WHO, 2019). Sebanyak 1-2% populasi pediatri menderita epilepsi sehingga epilepsi merupakan salah satu penyakit yang paling umum didiagnosis pada pediatri (Knupp, Koh and Park, 2012). Prevalensi kasus epilepsi pada pediatrik di Indonesia diperkirakan sekitar 40-50%.…”
Section: Pendahuluanunclassified
“…Childhood-onset epilepsy differs from epilepsy in adults not only in the clinical manifestations, including seizure type and epilepsy syndrome, but also in the presence of distinctive electroencephalogram (EEG) patterns, etiologies, and response to anti-seizure medication. The goals in treating epilepsy in children are complete control of their seizures, improvement of psychomotor development, and maintenance of quality of life for them and their family [ 3 ]. Previous follow-up studies [ 4 , 5 , 6 , 7 ] have reported that 60–70% of the patients with childhood-onset epilepsy entered remission under adequate treatment, and nearly half of them had sustained seizure remission following withdrawal of anti-seizure medication.…”
Section: Introductionmentioning
confidence: 99%